Detection of palmolein oil adulteration in milk fat using ATR-FTIR Spectroscopy and Chemometrics - Sonvanshi, Vivek; Gandhi, Kamal; Ramani, Akshay; Sharma, Rajan; Seth, Raman; mann, Bimlesh (Indian Journal of Dairy Science, 2025)
Clarified milk fat (ghee), a household staple in domestic India faces the threat of adulteration due to its economic value.  Examination of the purity of milk fat by chemical analysis is complex and time-consuming. The presence of palmolein oil in clarified milk fat was investigated using ATR-FTIR spectroscopy in combination with chemometric techniques. Spectral data within the wavenumber range of 4000-500 cm⁻¹ were obtained for pure ghee, palmolein oil, and spiked ghee samples at various palmolein oil concentrations (1, 3, 5, 10, 15, and 20%). PCA identified distinct spectral clustering patterns at specific wavenumbers (1167-1137 cm-1) at a 5% significance level, effectively separating pure ghee from adulterated samples. The SIMCA method yielded a remarkable 100% classification efficiency for both pure ghee and palmolein oil samples. Additionally, developed PLS and PCR models exhibited strong predictive accuracy, with high R2 values (0.96), enabling the detection of palmolein oil adulteration in ghee, even at concentrations as low as 1%. This research showcases the potential of ATR-FTIR with chemometrics analysis in ghee adulteration, offering a faster and more accurate routine analysis method.